Policy to Promote Technology Transfer: Experiences from China and Lessons for Vietnam - Hau Ngoc, Tran; Quoc Huy, Nguyen; Huu Xuyen, Nguyen (VNU Journal of Science: Policy and Management Studies; Vol 36 No 4DO - 10.25073/2588-1116/vnupam.4243, 2020)
China used to be considered as the world's factory, but up to now, China's technological capacity has made positive changes, showing the most clearly in decoding and mastering high technology. To achieve these achievements, the efforts of Chinese enterprises are not enough as they need support from the Government's policies to acquire and master technology through technology transfer. This paper focuses on researching policies to support China's technology transfer, thereby drawing lessons that are suitable to Vietnam's conditions in the context of a strong fourth industrial revolution.